Experience of being chair and co-chair of the ECMC and reasons why you should be the NEXT - Parkin, James (2023)
In this article, we provide an overview of the experience of being chair and co-chair of the Early Career Member Committee (ECMC) of the European Respiratory Society (ERS) from past and current officers – Niki Ubags (past chair), Maxime Patout (past co-chair), Sara Cuevas Ocaña (current chair) and Thomas Gille (current co-chair) (figure 1). The past chair and co-chair share their main achievements and challenges as leaders of the ECMC, and how the position has impacted (or is impacting) their career. The current chair and co-chair provide their view of the ECMC for the future and the goals to achieve during their mandate.